Affordance de conciliação e organizações híbridas: o papel das tecnologias da informação e comunicação na busca de um balanço das missões social e financeira dos Negócios de Impacto - Duarte, Hélida Mara Gomes Norato (2019)
This study addresses the intersection between Information Technology and Communication (ICT) and Business Impact in the strategic alignment of ICT. The affordance theory has been increasingly applied in studies that aim to analyze phenomena involving the interaction of technological and organizational systems. However, there are theoretical gaps in the adoption of affordance theory to analyze the strategic alignment of ICT with business functions, as well as to explore intersections between ICT and hybrid organizations such as Impact Business. The dialogue of this research with the existing literature had the intention of developing a theoretical approach on the results of the strategic alignment of ICT with the business functions through the affordance theory. The present thesis investigated the possibilities that ICT provides for hybrid organizations such as Impact Businesses. It sought answers to the following question: how do ICTs contribute to reconciling the dual mission (financial/social) in Impact Business? An empirical study - a cross-sectional analysis of the phenomenon - was developed through a set of semi-structured interviews with actors from various instances of the Impact Business ecosystem in Brazil. The main result is the introduction of the Affordance of conciliation concept as a positive potential of using ICT as a support structure, capable of favoring the conciliation of trade-offs in relation to organizational objectives. Developments to introduce this concept involved: (i) the identification of affordances that emerge from the unique dynamics of Impact Business; (ii) plausible explanation for a dimension in which varies the grade whereupon the mission and organizational objectives are supported by ICT. The theoretical proposition presented has the potential to support professionals in the development of projects aimed at innovative and assertive actions in favor of minimizing the asymmetries of a dual mission. For the students this proposition collaborates with three neglected points in the literature. First, it enriches the theory of affordance with the introduction of the concept of affordance of conciliation. Second, it provides support for the adoption of the affordance theory as an appropriate perspective for studies related to the strategic alignment of ICT with business functions. Finally, it provides support for exploring intersections between ICTs and hybrid organizations, such as Impact Business.